5q+6=2q+q+2

Since q is on the right side of the equation, switch the sides so it is on the left side of the equation.

2q+q+2=5q+6

Add 2q and q.

3q+2=5q+6

Subtract 5q from both sides of the equation.

3q+2-5q=6

Subtract 5q from 3q.

-2q+2=6

-2q+2=6

Subtract 2 from both sides of the equation.

-2q=6-2

Subtract 2 from 6.

-2q=4

-2q=4

Divide each term in -2q=4 by -2.

-2q-2=4-2

Cancel the common factor of -2.

Cancel the common factor.

-2q-2=4-2

Divide q by 1.

q=4-2

q=4-2

Divide 4 by -2.

q=-2

q=-2

Solve for q 5q+6=2q+q+2